Sistem Informasi Wisata Situs Batu Tulis Guna Meningkatkan Potensi Desa Ciaruteun Ilir, Kec. Cibungbulang, Kab. Bogor, Jawa Barat - Yudhy Setyo Purwanto; M. Farid Rifai; Hendra Jatnika; Sely Karmila (Terang, 2020)
Although it has been known for a long time the management of historical tourism potential of Situs Batu Tulis Ciaruteun has not been well categorized, because: 1) a simple management system, and still uses conventional and manual methods, especially for site information and cultural activities; and 2) The form of reservation and registration of entry into cultural/historical attractions still uses manual methods so that it influences the management and financial management of this site. These things cause the development of tourism objects to be hampered and in the end, become undeveloped. The potential for the development of cultural/historical tourism objects is very large considering the historical and cultural contributions that can be given. Data collection methods used are using observation, literature study and interviews, while the method of implementing activities is by creating a special website that combines 3 historical sites (Batu tulis, Tapak Gajah, dan Muara Cianten) which are located nearby. The solutions offered are: 1) creating a special website for cultural/historical attractions fot Situs Batu Tulis and its surroundings which contains historical information, cultural activities, and other activities; 2) create a management information system for reservation and registration of visits that is integrated with the website; and 3) provide training on the usages of the website and reservation and registration information system for village officials, youth groups, and object administrator. The contributions that will be felt by the surrounding community include: 1) improving the quality of life through economic empowerment including: welfare, hygiene, and health; 2) Increasing the popularity of the region which in turn can become the superior assets of region and province; and 3) increasing the understanding of history and culture of the surrounding community.